CRITICAL THINKING IS ESSENTIAL IN XXI CENTURY TEACHING. - Kambarov Shodiyorbek Shokirjon Ugli (Scholar Express Journal, 2023)
This article focuses on the issue of how critical thinking is important in teaching and the ways to develop significantly this skill with students in all stages of education. Furthermore there is some information about the features of critical thinking and the activities are given as samples for using in the classroom when the teachers develop their students` critical thinking abilities.
Keywords: Critical thinking; analyze information; digital world; develop the critical thinking skills